Research Methods Coverage in Medical and Health Science Curricula in Nepal - Simkhada, P; van Teijlingen, E; Pokharel, T; Devkota, B; Pathak, RS (Nepal Journal of Epidemiology, 2013)
Higher education institutions in Nepal have been offering different types of health sciences programmes over the last few decades. With the growing number of education institutions, the range of programmes has also increased. Currently, five higher education institutions – TU, KU, PU, PoU and BPKIHS are providing health sciences course at undergraduate and graduate level. TU being the leading university to offer most of health science programmes, there is observable influence in the curriculum contents and design of the remaining four institutions. However, a variation is observed in structure of curriculum within and between institutions. The curricula of Pokhara University are better designed and recent compared to other while the curricula of TU are less revised and comparatively old. Curricula in general health sciences are detailed and favourable to research methodology contents. DOI: http://dx.doi.org/10.3126/nje.v3i3.9185 Nepal Journal of Epidemiology 2013;3(3): 253-258